Major blunt thoracic trauma: Rotura de tráquea y bronquio fuente derecho - Gastambide, Carmelo; Croci, Fabio; Ruiz Liard, Alfredo; Pérez Penco, Ernesto; Schletter, Federico; Bounous, Walter (Cirugía del Uruguay, 1987)
. A case o! ruptJre of mediastinal !rachea extended to the main right bronchus due to a major blunt thoracic trauma, in a young man is presentad. lt was dianosed by liberbronchoscopy and operated on immediately with good results. Referred to this case an analysis of pathology, symptomatology, diagnostic and therapeutic procedures is done.